Barriers and facilitators of childhood COVID-19 vaccination among parents: A systematic review - Khan, Yusra Habib; Rasheed, Maria; Mallhi, Tauqeer Hussain; Salman, Muhammad; Alzarea, Abdulaziz Ibrahim; Alanazi, Abdullah Salah; Alotaibi, Nasser Hadal; Khan, Salah-Ud-Din; Alatawi, Ahmed D.; Butt, Muhammad Hammad; Alzarea, Sami I.; Alharbi, Khalid Saad; et al. (Frontiers in Pediatrics, 2022)
Background The acceptance of vaccination against COVID-19 among parents of young children plays a significant role in controlling the current pandemic. A wide range of factors that influence vaccine hesitancy in adults has been reported worldwide but less attention has been given to COVID-19 vaccination among children. Vaccine hesitancy is considered a major challenge in achieving herd immunity and it is more challenging among parents as they remain deeply concerned about their child`s health. Method A systematic search of peer-reviewed English literature indexed in Google Scholar, PubMed, Embase, and Web of science was performed using developed keywords between 1st January 2020, and August 2022. This systematic review included only those studies focused on parental concerns about COVID-19 vaccines in Children up to 12 years without a diagnosis of COVID-19. Following PRISMA guidelines, a total of 108 studies were included. The quality appraisal of the study was performed by Newcastle Ottawa Scale (NOS). Results The results of 108 studies depict that vaccine hesitancy rates differed globally with a considerably large number of factors associated with it. The highest vaccine hesitancy rates among parents were reported in a study from USA (86.1%), two studies from Saudi Arabia (>85%) and Turkey (89.6%). Conversely, the lowest vaccine hesitancy rates ranging from 0.69% and 2% were found in two studies from South Africa and Switzerland, respectively. The largest study (n=227,740) was conducted in Switzerland by Pastor et al., while the smallest sample size (n=12) was represented by a study conducted in the USA by Dube et al. The most commonly reported barriers to childhood vaccination were mothers' lower education level (N= 46/108, 43%) followed by financial instability (N= 19/108, 18%), low confidence in new vaccines (N=13/108, 12%) and unmonitored social media platforms (N= 5/108, 4.6%). These factors were significantly associated with vaccine refusal among parents. However, the potential facilitators for vaccine uptake among respondents who intended to have their children vaccinated include higher education level (N=12/108, 11%) followed by information obtained through healthcare professionals (N=9/108, 8.3%) and strong confidence in preventive measures taken by the government (N=5/81, 4.6%).